2012
DOI: 10.1111/j.1360-0443.2012.04027.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic disparities in HIV infection among people who inject drugs: an international systematic review and meta‐analysis

Abstract: Aims The Ethnic Minority Meta-Analysis (EMMA) aims to assess racial/ethnic disparities in HIV infection among people who inject drugs (PWID) across various countries. This is the first report of the data. Methods Standard systematic review/meta-analysis methods were utilized, including searching for, screening, and coding published and unpublished reports, and meta-analytic statistics. We followed the PRISMA Statement and MOOSE Guidelines for reporting methods. Disparities were measured with the odds ratio f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…While PWUDs, in general, have higher rates of several medical conditions, racial/ethnic minority PWUDs, in particular, face a disparate burden of HIV infection, decreased physical health and are less engaged in health care (Don C. Des Jarlais et al, 2012; Hall et al, 2013; Sanchez et al, 2015). In order to increase the number of PWUDs, and particularly racial/ethnic minority PWUDs, engaged in medical care, it is important to understand the factors that may deter them from initiating or remaining in medical care.…”
Section: Introductionmentioning
confidence: 99%
“…While PWUDs, in general, have higher rates of several medical conditions, racial/ethnic minority PWUDs, in particular, face a disparate burden of HIV infection, decreased physical health and are less engaged in health care (Don C. Des Jarlais et al, 2012; Hall et al, 2013; Sanchez et al, 2015). In order to increase the number of PWUDs, and particularly racial/ethnic minority PWUDs, engaged in medical care, it is important to understand the factors that may deter them from initiating or remaining in medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Although there remain regional and ethnic variations in prevalence rates, the inherent growing trend remains comparable worldwide. [12][13][14] They may occur alongside other forms of discrimination, such as racism, homosexuality or misogyny, prostitution, and drug abuse, and such associations complicate situation further because these are considered socially unacceptable in many parts of the world. 15,16 The concern for the developing world seems even greater.…”
Section: Introductionmentioning
confidence: 99%
“…Research on drug use and on people who use drugs often seems isolated from research on major societal trends, forces and conflicts even though these have been shown to affect many other health outcomes and behaviors (Des Jarlais et al, 2012; Drucker, 2011; Pickett & Wilkinson, 2009; Williams, 2012). This separation exists in part because much of this research focuses on individuals who use drugs (or do not do so) and on individual-level predictors of which individuals use drugs, how they use drugs, or the consequences of their drug use, and ignores macro-level structures and processes.…”
mentioning
confidence: 99%